Qualidade da luz na germinação de sementes de Tanchagem (Plantago major L.) em diferentes períodos de armazenamento - Souza, Brígida Savana de (2008)
The tanchagem (Plantago major L.) originated in Europe, but adapted themselves very well in Brazil and can be found in soil of almost the entire country. In Brazil is considered diuretic, anti-diarrheal, expectorante, hemostasis and healing, being employed against upper respiratory tract infections, chronic bronchitis and as an aid in the treatment of peptic ulcers. For national conditions, few studies have been conducted so far, with seeds of medicinal species. It appears that these species light is needed for germination of seeds and development of many plants. Another factor that contributes to the success of germination is the seed storage that is a step which should seek to reduce the maximum speed and intensity of the process of deterioration. The work was done in the laboratory for analysis of Seeds of UFERSA to assess the influence of the quality of light in the germination of seeds of tanchagem (Plantago major L.) in different periods of storage. The experimental design was a completely randomized, factorial 4 x 4, representing the first factor the quality of light (white light, red light, red light and extreme lack of light), and the second the period of storage (zero, two , Four six months), with four repetitions of 50 seeds. The characteristics evaluated were the first count, and the percentage of germination rate of speed germination. In this experiment there was significant interaction between the types of light and the periods of storage for all the characteristics analyzed. The seeds of tanchagem showed low germination. The absence of light influences in the first count (PC), percentage of germination (PG) index and speed of germination (IVG), seeds of this species. The red and white light